Conidial Density and Viability of Beauveria bassiana Isolates from Java and Sumatra and Their Virulence Against Nilaparvata lugens at Different Temperatures - Sumikarsih, Eka; Herlinda, Siti; Pujiastuti, Yulia (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
The brown planthopper (BPH), Nilaparvata lugens can cause direct damage and transmit rice diseases. Beauveria bassiana is used to control BPH, however the success of the fungal efficacy on rice fields is affected by external factors, such as temperature. This research aimed to evaluate the conidial viability and density of B. bassiana isolates from Java and Sumatra, exposed to 25 and 34°C and their virulence against BPH nymphs. Twenty six isolates of B. bassiana cultures incubated at 25 and 34°C for 7 days were observed on their conidial density, viability, and virulence against BPH nymphs. The incubation temperature of 34°C was able to decrease conidial density and viability, and virulence of the isolates. However, some isolates of B. bassiana originated from soils or insects in Sumatra, especially from South Sumatra still produced high conidial density and viability as well as high virulent against BPH nymphs, such as TS1D3A, TSID3B, TS1D2A and TS1D2B isolates. The TS1D2B isolate incubated at 34°C still caused the highest percentage of BPH mortality (43.33%) among other isolates. Therefore, the isolates can be used as promosing candidate for biocontrol for N. lugens on rice planted in tropical ecosystem, such as wetland or lowland rice ecosystems in Indonesia.